Adaptive benchmarking design for additive manufacturing processes. (1st June 2022) - Spitaels, Laurent; Rivière-Lorphèvre, Edouard; Demarbaix, Anthonin; Ducobu, François
Abstract: Standards enabling the objective tolerancing and evaluation of dimensional and geometrical performances of additive manufacturing (AM) printers are still missing. The design, printing and measurements of geometrical benchmark test artefacts (GBTA) is the current solution proposed in literature. However, the current GBTA with fixed dimensions cannot cover most of the available printing area of printers with large building platform dimensions. This article proposes to solve this problem by developing an adaptive GBTA design whose main dimensions can be adapted to any common 3D printer. Moreover, an innovative design is implemented to decrease the risk of warping. The adaptive GBTA will then be used to characterise the performances of two different architecture material extrusion printers (Ultimaker 2+ and Pollen AM Series MC). Dimensional and geometrical accuracy, as well as top surface topography, were evaluated. The Ultimaker printer could reproduce features with maximum deviations below the tolerance interval (IT) 13 of the ISO 286-1, while the Pollen machine achieved a higher IT of 15 or 16. The highest geometrical deviations were observed for the coaxiality of cylinders oriented along the build direction (Ultimaker: 0.250 mm and Pollen: 0.497 mm). Top surface topography exhibited higher Ra values for Pollen (13.7 µm) than for Ultimaker 2+ (4.9 µm). The performances of the Pollen printer were lower than the Ultimaker machine in terms of surface topography, dimensional and geometrical accuracy. The proposed adaptive GBTA design covers most of the printing areas exhibited by Pollen and Ultimaker printers and offers flexibility to test other printers even with larger or smaller dimensions.